Effect of fiber loading on the flexural and tensile strength of oil palm frond fiber reinforced polymer composite - Richard, Beatrice Dimah; Wahi, Azizah; Nani, Rozie; Lling, Elisha; Osman, Shahril; Ali, Dayang Siti Hazimmah (International Journal of Integrated Engineering, 2019)
Research on composite have been widely done throughout the world. Incorporation of reinforcing materials into matrix can one day replace the use of conventional materials such as polymers, metals, ceramics and woods. In this research, a composite made of oil palm frond fiber and urea formaldehyde is fabricated. As oil palm frond fiber can be obtained in great amount due to high amount of wastage generated, composite can be a way to reduce this wastage. There are two different type of fiber loading which is 40% and 50%. The fiber and UF are mix until it is homogenous. It is then placed into the hot press machine to undergo hot press process. After the fabrication, the mechanical properties of the composite will be tested and observed. The mechanical test includes flexural and tensile test. Both tests are done in accordance to the ASTM standard which are ASTM D-790 and ASTM D-638. The morphological characteristic of the composite will also be observed in this study. The results show that the composite with higher fiber loading, which is 50 %, have better mechanical properties. The composite with 50 % of fiber has a flexural strength of 1.4306 MPa, a modulus of elasticity of 1248.9516 MPa and a tensile strength of 3.874 MPa. These composites can be used as an alternative for wood and automotive application.